2016
DOI: 10.1080/21553769.2016.1233909
|View full text |Cite
|
Sign up to set email alerts
|

Suggested mechanism for the effect of sweeteners on radical scavenging activity of phenolic compounds in black and green tea

Abstract: The present work aims to evaluate the relation between the antioxidant activities and phenolic compound contents of two tea samples (green and black) mixed with or without sweeteners (sucrose or aspartame). The aqueous extracts were screened for total polyphenol and flavonoids contents. Antioxidant activities of extracts were tested using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical method and 2, 2 -azino-bis [ethylbenzthiazoline-6-sulfonic acid] (ABTS) methods using butylated hydroxyl anisole as standard com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 34 publications
8
21
0
Order By: Relevance
“…This phenomenon might be caused by a possible condensation reaction between the hydroxyl groups in sucrose molecule and the hydroxyl group of phenolic compounds in MEPPE and formation of the glycoside. The similar result was observed by Shalaby et al (2016). Table sugar addition caused a significant reduction in antioxidant activity of green tea using two tested methods (DPPH and ABTS radical).…”
Section: Antioxidant Activitiessupporting
confidence: 86%
See 1 more Smart Citation
“…This phenomenon might be caused by a possible condensation reaction between the hydroxyl groups in sucrose molecule and the hydroxyl group of phenolic compounds in MEPPE and formation of the glycoside. The similar result was observed by Shalaby et al (2016). Table sugar addition caused a significant reduction in antioxidant activity of green tea using two tested methods (DPPH and ABTS radical).…”
Section: Antioxidant Activitiessupporting
confidence: 86%
“…The similar result was observed by Shalaby et al . (). Table sugar addition caused a significant reduction in antioxidant activity of green tea using two tested methods (DPPH and ABTS radical).…”
Section: Resultsmentioning
confidence: 97%
“…Additionally, the inconsistent trend in antioxidant activity change can be attributed to various reasons, including the hydrolysis of the flavonoid glycosides, delivering an additional -OH moiety that can react with the ABTS cation radical [32]. Moreover, the interaction of the phenolic compounds or their oxidized form with the sugar molecules and the consequent formation of the reduced form of phenolic compounds that can interact with ABTS radicals [35] orto a lesser extent-the presence of non-polyphenol antioxidants can also contribute to the observed lack of correlation between polyphenol content and ABTS radical scavenging activity obtained in our study. Other authors attribute the phenomenon to other factors, such as increased antioxidant power of polyphenols at an intermediate state of oxidation, increase in reducing sugar and formation of Maillard products, known to show a high antioxidant activity, which is often exerted in mechanisms similar to that of the ABTS assay [36].…”
Section: Total Soluble Solids Total Polyphenol Content and Antioxidamentioning
confidence: 99%
“…The same is observed when comparing P+US (315.42 ± 1.76 µmol TE/L) on day 0 to K+S+US (282.66 ± 11.22 µmol TE/L) and K+US (305.87 ± 0.85 µmol TE/L) on day 5. Shalaby et al (2016) reported a decrease in antioxidant activity in green tea with addition of sucrose potentially attributable to the condensation reaction between hydroxyl groups of phenolics and sucrose molecules to form glycosides. No significant difference was observed in ORAC between P (298.30 ± 2.35 µmol TE/L), P+US (300.40 ± 1.58 µmol TE/L), K+US (308.98 ± 8.15 µmol TE/L) and K+S+US (289.09 ± 5.97 µmol TE/L) on day 21 while K (280.01 ± 7.18 µmol TE/L) and K+S (283.39 ± 14.06 µmol TE/L) had significantly lower ORAC values.…”
Section: Dornan Et Almentioning
confidence: 99%